Single-crystal growth of organic semiconductors - Jiang, Hui (2014)
Organic single crystals are an established part of the emerging field of organic optoelectronics, because they provide an ideal platform for the studies of the intrinsic physical properties of organic semiconductors. As organic crystals have low melting temperatures and high vapor pressures and are soluble in numerous organic solvents, both solution and gas-phase methods can be used for crystal growth. The nature of the individual molecules and the interactions between molecules determine which growth method is preferred for particular materials. Organic semiconductors with very low decomposition or melting temperatures can be grown from solutions, whereas semiconductors with high vapor pressures can be grown using physical vapor transport methods. High-quality crystals can be obtained using both methods. Crystal growth and crystal engineering of multicomponent organic compounds are emerging fields that can provide a variety of new materials with different physical properties. The growth of large crystals from the melt by zone melting, the Bridgman, or the Czochralski methods has been used to produce stable materials used in wafer manufacturing or large scintillator detectors. In this article, single-crystal growth methods for organic semiconductors are discussed with the aim of preparing high-quality specimens for determination of the basic properties of organic semiconductors.